Metabolomics reveals altered metabolites in cirrhotic patients with severe portal hypertension in Tibetan population - Ye, Yanting; Xia, Chao; Hu, Hong; Tang, Shihang; Huan, Hui (Frontiers in Medicine, 2024)
Background: Portal hypertension (PHT) presents a challenging issue of liver cirrhosis. This study aims to identify novel biomarkers for severe PHT (SPHT) and explore the pathophysiological mechanisms underlying PHT progression.Methods: 23 Tibetan cirrhotic patients who underwent hepatic venous pressure gradient (HVPG) measurement were included. 11 patients had an HVPG between 5 mmHg and 15 mmHg (MPHT), while 12 had an HVPG ≥ 16 mmHg (SPHT). Peripheral sera were analyzed using liquid chromatograph-mass spectrometer for metabolomic assessment. An additional 14 patients were recruited for validation of metabolites.Results: 745 metabolites were detected and significant differences in metabolomics between MPHT and SPHT patients were observed. Employing a threshold of p < 0.05 and a variable importance in projection score > 1, 153 differential metabolites were identified. A significant number of these metabolites were lipids and lipid-like molecules. Pisumionoside and N-Decanoylglycine (N-DG) exhibited the highest Area Under the Curve (AUC) values (0.947 and 0.9091, respectively). Additional differential metabolites with AUC > 0.8 included 6-(4-ethyl-2methoxyphenoxy)-3,4,5-trihydroxyoxane-2-carboxylic acid, Sphinganine 1-phosphate, 4hydroxytriazolam, 4,5-Dihydroorotic acid, 6-Hydroxy-1H-indole-3-acetamide, 7alpha-(Thiomethyl)spironolactone, 6-Deoxohomodolichosterone, Glutaminylisoleucine, Taurocholic acid 3-sulfate, and Phe Ser. Enzyme-linked immunosorbent assay further confirmed elevated levels of Sphinganine 1-phosphate, N-DG, and serotonin in SPHT patients. Significant disruptions in linoleic acid, amino acid, sphingolipid metabolisms, and the citrate cycle were observed in SPHT patients.Pisumionoside and N-DG are identified as promising biomarkers for SPHT. The progression of PHT may be associated with disturbances in lipid, linoleic acid, and amino acid metabolisms, as well as alterations in the citrate cycle.